Keadilan Dan Hak Asasi Dalam Terang Fajar Filsafat Islam - Radiyatun Adabiyah (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2022)
In order to seek the nature of human rights in Islamic philosophy, it will not be able to understood until clarify the overall Islamic concept of nature, humans and life. As it is also known that the essence of justice cannot be separated from the relationship that occurs between the Creator and creatures. Justice also becomes very important in law, because it is subjective and individual. Justice as a value to create an ideal relationship between humans, as a manifestation of their rights. In this case, justice is the basis that is committed to delivering humans to a just, prosperous and happy life. As it is known that the practice of law in the western sense is really in accordance with the special attention of some experts in Islamic law. The meaning of Islamic philosophy itself cannot be separated from the Greek teachings which are collaborated with the contents of the explanations/teachings in Islam. So the discussion on human rights will not be separated from the discussion of Epistemology, Ontology and Axiology. It is well known that philosophy itself will not be separated from logic, because the context of the discussion of philosophy will continue to change as a civilization develops. If we mention about Islamic philosophy, we will know how the nature of justice is seen from the perspective of logic that is shaded by the Islamic side. How that sense works well in determining an acceptable justice for the welfare of human rights. It has also been stated that humans are intelligent animals, so humans are different from other animals in general. Intellect is a benchmark for the perfection of a human action in deciding something. Justice for human rights in the view of Islamic philosophy is justice for human rights which is applied in accordance with mature thinking and cannot be separated from the teachings of the Qur'an and Sunnah.